The Hala Kahiki / Nur Hadirah Rahim ... [et al.] - Rahim, Nur Hadirah; Khalid Khan, Nur Syuhada; Mohammad Tamil, Nor Eka Najwa; Mohamed, Abdul Hamid (2024)
In educational institutions, public areas are vital for promoting students' health, creativity, and academic achievement. This abstract provides a framework for designing dynamic public spaces that prioritize students and accurately cater to their needs and preferences. Comprehending the heterogeneous requirements and inclinations of learners is fundamental to efficiently designing public areas. It is important to carefully consider factors like age, cultural background, and academic interests when designing spaces that connect students and strengthen their sense of community and belonging. It is possible to create public areas that promote relaxation, teamwork, and social contact by applying the principles of human-centred design. Interactive installations, dedicated zones for group study or leisure activities, and flexible seating arrangements can accommodate diverse types of involvement and a range of preferences.